Microfluidic rapid and autonomous analytical device (microRAAD) to detect HIV from whole blood samples. Issue 20 (20th September 2019) - Phillips, Elizabeth A.; Moehling, Taylor J.; Ejendal, Karin F. K.; Hoilett, Orlando S.; Byers, Kristin M.; Basing, Laud Anthony; Jankowski, Lauren A.; Bennett, Jackson B.; Lin, Li-Kai; Stanciu, Lia A.; Linnes, Jacqueline C.
Abstract : This handheld sample-to-answer platform combines blood cell separation, viral lysis, and isothermal nucleic acid amplification with capillary fluidics and heating controls to automatically detect HIV from blood samples within 90 minutes. Abstract : While identifying acute HIV infection is critical to providing prompt treatment to HIV-positive individuals and preventing transmission, existing laboratory-based testing methods are too complex to perform at the point of care. Specifically, molecular techniques can detect HIV RNA within 8–10 days of transmission but require laboratory infrastructure for cold-chain reagent storage and extensive sample preparation performed by trained personnel. Here, we demonstrate our point-of-care microfluidic rapid and autonomous analysis device (microRAAD) that automatically detects HIV RNA from whole blood. Inside microRAAD, we incorporate vitrified amplification reagents, thermally-actuated valves for fluidic control, and a temperature control circuit for low-power heating. Reverse transcription loop-mediated isothermal amplification (RT-LAMP) products are visualized using a lateral flow immunoassay (LFIA), resulting in an assay limit of detection of 100 HIV-1 RNA copies when performed as a standard tube reaction. Even after three weeks of room-temperature reagent storage, microRAAD automatically isolates the virus from whole blood, amplifies HIV-1 RNA, and transports amplification products to the internal LFIA, detecting as few as 3 × 10 5 HIV-1 viral particles, or 2.3 × 10 7 virus copies per mL of whole blood, within 90 minutes. This integrated microRAAD is a low-cost and portable platform to enable automated detection of HIV and other pathogens at the point of care.